Evaluasi Perilaku (Consumer Behavior) Pengguna Dan Operator Angkutan Umum Perkotaan - Atun, Sri (Warta Penelitian Perhubungan, 2010)
In the context of public transport and urban areas, the main problem faced is traffic congestion. Ihismn be mused m; many things, such as traffic discipline is relatively low, not optimal role has not beenimplemented angktuan general and mass transit in urban areas optimally. Conduct public Searaurban transport users have not shown good discipline. On the other side of the urban public transportavailable was impressed not planned on a needs basis. Type of public transportation in some areascontinue to grow with the reason for fleet renewal, while tlze aging of the existing jl.&t is still operating.Condud public transport operators in urban areas seem to find profit without regard to rules that should be applied.